Successful orthodontic treatment of Class II division 1 malocclusion in a non growing patient : A case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Aim & objectives of the present case report was to evaluate the management of skeletal Class II division 1 malocclusion in non growing patient with extraction of upper first premolars. Clinical and cephalometric evaluation revealed skeletal Class II division 1 malocclusion with severe maxillary incisor proclination, convex profile, average mandibular plane angle, incompetent lips, increased overjet and overbite. After extraction of upper 1st premolars, canine retraction was done which was followed by retraction of severely proclined upper anterior teeth by judicious control of third order bend in rectangular stainless steel arch wire with V loop . For anchorage management, intra oral anchorage with tip back & toe in bends in stainless steel arch wire was satisfactory. Following treatment marked improvement in patients smile, facial profile and lip competence were achieved and there was a remarkable increase in the patients confidence and quality of life. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16165 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 41-45